Reformulating the Boundaries of Freies Ermessen: An Analysis of Conflict of Norms in the Government Administration Law Post-Enactment of the Job Creation Law - Sari, Triana Galuh Purnama (CV. Social Politic Genius (SIGn), 2025)
The paradigm shift in Indonesian administrative law following the enactment of Government Regulation in Lieu of Law Number 2 of 2022 has created serious legal issues regarding the validity of discretion (Freies Ermessen). The elimination of the requirement that “not contrary to the provisions of laws and regulations” in Article 24 of Law Number 30 of 2014 creates an internal conflict with the Principle of Legal Certainty. Furthermore, this amendment blurs the demarcation boundary between administrative error (maladministration) and corruption offenses. This potentially leads to policy criminalization. This research aims to analyze the juridical implications of such norm change and to reconstruct the boundaries of public official liability using the parameters of mens rea and ultimum remedium. This study is normative legal research employing statutory, conceptual, and comparative approaches. The results indicate that the absence of formal legality parameters demands a shift in the focus of discretion validity testing toward a substantive aspect. Such focus encompasses compliance with the objectives of discretion and the general principles of good governance. The strict boundary between the administrative and criminal realms lies in proving the element of mens rea for unlawfully enriching oneself. Therefore, criminal law must be positioned as the ultimum remedium after administrative testing mechanisms through the Government Internal Supervisory Apparatus and the State Administrative Court have been exhausted. This research recommends adopting the reasonableness test in discretion testing to provide legal certainty and protection for officials when innovating.